Cloud Computing in Science and Engineering and the “SciShop.ru” Computer Simulation Center - Tarnavsky, G. A.; Vorozhtsov, E. V. (Engineering, Technology & Applied Science Research, 2011)
Various aspects of cloud computing applications for scientific research, applied design, and remote education are described in this paper. An analysis of the different aspects is performed based on the experience from the “SciShop.ru” Computer Simulation Center. This analysis shows that cloud computing technology has wide prospects in scientific research applications, applied developments and also remote education of specialists, postgraduates, and students.